The Influence of Service Quality and Tax Sanctions on Taxpayer Compliance - Putra, Loist Abdi; Loist, Christine; Butarbutar, Novita; Efendi, Efendi; Sudirman, Acai (IJBLE Scientific Publications Community Inc., 2023)
Taxpayer compliance has many positive and important impacts on the government and society. Research on service quality and tax sanctions on taxpayer compliance can provide valuable insight into understanding the factors that influence the level of taxpayer compliance. This research aims to analyze the influence of service quality and tax sanctions on taxpayer compliance. Data analysis confirms that service quality and tax sanctions significantly affect taxpayer compliance in paying taxes. The conclusions of this research inform an effective tax education and socialization program that can help taxpayers understand the importance of compliance and the positive impact of tax payments in supporting development. Clear and effective communication between tax authorities and taxpayers can help prevent misunderstandings and uncertainty hindering compliance. Proportionality in the application of sanctions is important so that the sanctions are appropriate to the level of the violation. This creates a sense of fairness and can prevent taxpayers from feeling treated unfairly. Giving tax authorities the power to impose sanctions increases their capacity to enforce tax rules.